2007
DOI: 10.1007/s11947-007-0038-6
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Wheat and Maize Flours Properties on the Expansion Mechanism During Extrusion Cooking

Abstract: The expansion mechanism in the extrusion cooking process was investigated during maize and wheat flours processing in a twin-screw extruder. An experimental study of extrusion process was carried out at constant moisture and specific mechanical energy. The expansion phenomenon which consists in a growth phase followed by a shrinkage phase was observed through an image processing method and analyzed by use of classical expansion indices: sectional, longitudinal and volumetric expansion indices. It was found tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
23
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(23 citation statements)
references
References 23 publications
0
23
0
Order By: Relevance
“…This can be justified as increase in the share of cornmeal in the mixture (typical structure building ingredient) contributes to growth in expansion parameters (e.g. radial expansion) of many extruded cereal ingredients, including wheat [10,17]. Therefore, based on the analysis of a single factornamely, the area of photographed products -one can state whether change in process parameters involves any change in external "visual" quality parameters of the extrudates Figures 3a and 3b illustrate changes in the extrudate Eongation Factor.…”
Section: Resultsmentioning
confidence: 99%
“…This can be justified as increase in the share of cornmeal in the mixture (typical structure building ingredient) contributes to growth in expansion parameters (e.g. radial expansion) of many extruded cereal ingredients, including wheat [10,17]. Therefore, based on the analysis of a single factornamely, the area of photographed products -one can state whether change in process parameters involves any change in external "visual" quality parameters of the extrudates Figures 3a and 3b illustrate changes in the extrudate Eongation Factor.…”
Section: Resultsmentioning
confidence: 99%
“…Thus, starch may have binding properties in pelleted feeds. The role of extrusion process variables on the expansion volume of cereals or starches has been already investigated (Faubion et al, 1982;Meuser et al, 1982;Launay and Lisch, 1983;Owusu-Ansah et al, 1983;Chinnaswamy and Hanna, 1988;Lai and Kokini, 1991;Jeong et al, 1991;Arhaliass et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…During extrusion cooking, raw materials undergo various chemical and structural transformations. Additionally, the product quality can vary considerably depending on the extrude type, screw configuration, feed moisture, temperature profile in the barrel, and screw speed (Arhaliass et al, 2009;Oluwole et al, 2013;W³odarczyk-Stasiak et al, 2009;Stasiak et al, 2012). Tarathanos and Saravacos (1993) found that gelatinized starches have average pore sizes of 0.8-1.5 mm and bulk porosity lower than 0.1 cm 3 g -1 .…”
Section: Introductionmentioning
confidence: 99%